Illegal Dumping of Toxic Waste and Its Effect on Human Health in Campania, Italy - Mazza, Alfredo (Int J Environ Res Public Health, 2015)
The region of Campania (particularly Naples and Caserta) has experienced an emergency in the waste management cycle during past years. Although the most critical phase has been overcome after the construction of the incineration plant in Acerra (an old-fashioned technology built up over a few months, whose impact on environment and health has not yet been assessed), most of the underlying problems have not been resolved. The illegal burning of wheels, plastics, textiles, and other industrial residuals, along with the detection of two thousand toxic substance dumping sites, still represents major concerns of environmental pollution and population health. This review summarizes the most relevant studies, which analyzed chemical contamination (primarily dioxins and polychlorinated biphenyls (PCBs)) of the air, soil, water, animals, and humans in Campania. In addition, we reviewed information on population health (i.e., mortality data, congenital malformations, and cancer incidence). Moving from a detailed mapping of (mostly illegal) waste dumping sites in Campania, we have focused on recent studies which have found: (a) high concentrations of dioxins (≥5.0 pg TEQ/g fat) in milk samples from sheep, cows, and river buffaloes; (b) remarkable contamination of dioxin and PCBs in human milk samples from those living in the Naples and Caserta areas (PCDDs+PCDFs and dioxin-like-PCBs (dl-PCBs) assessed at 16.6 pg TEQ/g of fat; range: 7.5–43 pg/g of fat); (c) potential age-adjusted standardized mortality rates associated with some specific cancer types; (d) a statistically significant association between exposure to illegal toxic waste dumping sites and cancer mortality, even after adjustment by socio-economic factors and other environmental indicators.